Isolect Language Status of Wakatobi Language in the Sikka Islands (A Dialectological Study) - Hamid, Abdul; Mboka, Idris (Budapest International Research and Critics University, 2021)
Each language has a variety of language variations because it is influenced by geographical conditions. The BWKS isolect gives rise to different lexicons based on geographical location. This study aims to describe the differences in the lexicon and determine the isolect status of BWKS. This research was conducted in 6 BWKS isolect-speaking areas in Sikka Regency. The method used in this research is descriptive qualitative and quantitative methods. The data collection method is a proficient method with structured interview techniques (structured interview). The technique of data analysis is the Differential Comparative Relationship (HBB) technique. The results showed that there were 21 different BWKS isolect lexicon vocabularies. Based on the results of the dilatometry calculation, it can be stated that the linguistic status of the BWKS isolect is no different. The percentage of BWKS Isolect vocabulary ranges from 0% - 20%. The highest percentage of BWKS Isolect vocabulary distance is 5.25%. These results are found in the comparison between TP including TP 1-3, 1-4, 2-4. While the percentage of the lowest BWKS Isolek word distance is 0%. These results are found in the comparison between TP including TP 1-2, 3-4, 3-5, 4-5, 4-6, and 5-6.